2016
DOI: 10.1586/14737159.2016.1141678
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the practical implementation of POCT: overcoming challenges

Abstract: There are many challenges in implementing a successful point-of-care testing (POCT) program. When compared to traditional testing, POCT results are faster and allow for rapid patient treatment. Unfortunately, the excitement of this technology is often lost due to an assortment of practical obstacles. Implementation of POCT requires consideration of the regulatory complexity and amount of documentation to be compliant. As more tests move to the site of patient care, the number of operators that need to be train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…In this review, a medical test is considered point of care if it meets two criteria: it is performed near where the patient is being seen and it takes 15 min or less to obtain results. They are often carried out in a manner that allows a patient to be examined, tested, and prescribed within the same visit [165]. These methods help clinicians to decide the specific treatment regimens by elucidating the specific pathogen and/or any resistances that the pathogen may be harboring [166].…”
Section: Point Of Care and Resistance Susceptibility Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, a medical test is considered point of care if it meets two criteria: it is performed near where the patient is being seen and it takes 15 min or less to obtain results. They are often carried out in a manner that allows a patient to be examined, tested, and prescribed within the same visit [165]. These methods help clinicians to decide the specific treatment regimens by elucidating the specific pathogen and/or any resistances that the pathogen may be harboring [166].…”
Section: Point Of Care and Resistance Susceptibility Testingmentioning
confidence: 99%
“…Many hospitals only offer POCT or resistance susceptibility testing after a patient has shown negative progress during a first-line treatment due to the costs associated with the time, personnel, and equipment associated with performing these tests [165]. This also means that there is a disparity in the clientele that can have the tests performed, leading to a high degree of socioeconomic discrepancy in access [165,[167][168][169]. Weihser and Giles showed that an increase in the use of POCT in ambulatory care, in essence, an earlier timepoint, reduces the overall number of patient bed days spent in the hospital.…”
Section: Point Of Care and Resistance Susceptibility Testingmentioning
confidence: 99%
“…The detection sensitivity of pathogen nucleic acid POCT is higher than that of immunological POCT ( Basile et al., 2018 ; Nelson et al., 2020 ; Song et al., 2021 ; Wang et al., 2021 ), and the use of inexperienced personnel in molecular detection carries the risk of detection failure and environmental cross-contamination ( Wiencek and Nichols, 2016 ). For example, in a clinic or public space where the flu vaccine or SARS-CoV-2 vaccine is administered, contaminated equipment will produce false positives.…”
Section: Limitations Of Poct Nucleic Acid Detectionmentioning
confidence: 99%
“…Point-of-care tests (POCTs) to enable to rapid and appropriate management of sexually transmitted infections (STIs) have potential to positively impact infection control, disease progression, and patient perceptions of clinical services (1)(2)(3). Despite the potential advantages STI POCTs may bring, their launch into market will not necessarily lead to their adoption into clinical services; many POCTs have struggled to be purchased, implemented and integrated ("adopted") into healthcare (4,5). Guidance for adoption of new diagnostics into clinical care are usually premised on evidence-based medicine (EBM), which is predicated on robust clinical research determining best clinical practice (6,7).…”
Section: Introductionmentioning
confidence: 99%